Predicting Non-Alcoholic Fatty Liver Disease Progression and Immune Deregulations by Specific Gene Expression Patterns - Zeng, Fanhong; Zhang, Yue; Han, Xu; Zeng, Min; Gao, Yi; Weng, Jun (Frontiers in Immunology, 2021)
Non-alcoholic fatty liver disease (NAFLD) is the most common liver disease worldwide with rising rates in parallel to obesity, type 2 diabetes and metabolic syndrome. NAFLD includes pathologies ranging from simple steatosis (NAFL) to non-alcoholic steatohepatitis and cirrhosis (NASH), which may eventually develop into hepatocellular carcinoma (HCC). Mechanically, lipids accumulation and insulin resistance act as the first hit, inflammation and fibrosis serve as the second hit. Currently, the diagnosis of NAFLD mainly depends on pathology examination and medical imaging, whereas proper gene signature classifiers are necessary for the evaluation of disease status. Here, we developed three signature classifiers to distinguish different NAFLD disease states (NAFL and NASH). Moreover, we found B cells, DCs, and MAIT cells are key deregulated immune cells in NAFLD, which are associated with NAFLD and NAFLD-HCC progression. Meanwhile, AKR1B10 and SPP1 are closely related to above three immune cell infiltrations and immunosuppressive cytokines expressions in NAFLD and NAFLD-HCC. Subsequently, we screened out AKR1B10 and SPP1 sensitive molecules TGX-221, which may provide a possible therapy for NAFLD and NAFLD-HCC.